2021
DOI: 10.3390/nano11102632
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Non-Animal Testing Approaches towards Accelerated Clinical Translation of Novel Nanotheranostic Therapeutics for Central Nervous System Disorders

Abstract: Nanotheranostics constitute a novel drug delivery system approach to improving systemic, brain-targeted delivery of diagnostic imaging agents and pharmacological moieties in one rational carrier platform. While there have been notable successes in this field, currently, the clinical translation of such delivery systems for the treatment of neurological disorders has been limited by the inadequacy of correlating in vitro and in vivo data on blood–brain barrier (BBB) permeation and biocompatibility of nanomateri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 239 publications
(284 reference statements)
0
6
0
Order By: Relevance
“…The increased complexity in the elaboration of the devices verified in this review (18.2% level IV [ 41 , 44 , 46 , 56 ], 40.9% level III [ 45 , 47 , 48 , 50 , 51 , 53 , 54 , 55 , 57 , 59 , 60 ], and 36.4% level II [ 39 , 40 , 43 , 49 , 58 ]) has reflected the diversity of components present in the real tumor microenvironment, as well as the responses obtained from the interaction of the different systems, cells and ECM, as described in the study by Jo et al [ 50 ] that observed chemoresistance regarding the use of Matrigel in the treatment with DOX, among other aspects. In this sense, the literature has proven that the responses of organ-on-a-chip studies have been increasingly closer to in vivo studies than the results obtained in in vitro [ 86 , 87 ], and represents an excellent platform for validation of therapeutic processes for glioblastoma tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The increased complexity in the elaboration of the devices verified in this review (18.2% level IV [ 41 , 44 , 46 , 56 ], 40.9% level III [ 45 , 47 , 48 , 50 , 51 , 53 , 54 , 55 , 57 , 59 , 60 ], and 36.4% level II [ 39 , 40 , 43 , 49 , 58 ]) has reflected the diversity of components present in the real tumor microenvironment, as well as the responses obtained from the interaction of the different systems, cells and ECM, as described in the study by Jo et al [ 50 ] that observed chemoresistance regarding the use of Matrigel in the treatment with DOX, among other aspects. In this sense, the literature has proven that the responses of organ-on-a-chip studies have been increasingly closer to in vivo studies than the results obtained in in vitro [ 86 , 87 ], and represents an excellent platform for validation of therapeutic processes for glioblastoma tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Mature DC cultured in vitro can induce other immune cells to migrate to the tumor site by chemokines, thus improving the immune microenvironment of patients. 92 The mRNA levels of both CCL10 and TLR3 were significantly upregulated after the first and fourth DC vaccination, and CCL10 could guide CD8+ T cells into brain tumor sites, 93 thus improving the inhibitory immune microenvironment in glioma patients. 94 Hirokazu Ogino et al pretreated DCs with poly‐ICLC and found that in addition to upregulating cytokines such as IFN‐γ, TNF‐α, and IL‐10, 95 the migration of effector memory CD8+ T cells in the TME may be mediated through the CXCL10/CXCR3 axis, 96 which showed the activating DCs can effectively improve the migration of other immune cells and improve the tumor microenvironment by regionalization factors.…”
Section: Influence Of DC Vaccines On the Immune Mi...mentioning
confidence: 99%
“…Mature DC cultured in vitro can induce other immune cells to migrate to the tumor site by chemokines, thus improving the immune microenvironment of patients 92 . The mRNA levels of both CCL10 and TLR3 were significantly upregulated after the first and fourth DC vaccination, and CCL10 could guide CD8+ T cells into brain tumor sites, 93 thus improving the inhibitory immune microenvironment in glioma patients 94 .…”
Section: Influence Of DC Vaccines On the Immune Microenvironment Of G...mentioning
confidence: 99%
“…In this line, smart drug delivery systems might offer several advantages in comparison to traditional drug delivery systems. Further details are included in the extensive review from Lynch and Gobbo, in which the advantages of nanoparticle-based smart drug delivery systems crossing through the BBB versus traditional drug delivery systems are deeply discussed [25]. Briefly, ligand decoration is crucial to ensure an optimum transcellular transport of the nanomedicine, especially to promote receptor-mediated transcytosis, which is the most used method for intracerebral delivery.…”
Section: Challenges In Drug Delivery To the Cnsmentioning
confidence: 99%
“…However, Lynch and Gobbo also pointed out the issues for clinic translation, mainly related to the lack of realistic models [25]. Intracerebral drug delivery then faces two great challenges.…”
Section: Challenges In Drug Delivery To the Cnsmentioning
confidence: 99%